"Dumia Umbanua” : Misi Kontekstual Dalam Moderasi Beragama Di Desa Laikit Kabupaten Minahasa Utara - Royke Lantupa Kumowal; Heliyanti Kalintabu; Charolin Geby Bambung (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
The dumia umbanua tradition has important historical and cultural values ​​for the local community. However, the implementation of the Dumia Umbanua traditional ceremony often gives rise to differences in views and interpretations between custom and religion, as well as giving rise to conflict between communities. Some Christian religious figures in Minahasa even consider that the dumia umbanua traditional ceremony is not in accordance with the Christian faith. The aim of this research is to examine the dumia umbanua tradition; connecting dumia umbanua in the study of contextual mission theology and implementation in religious moderation. The research method used is a descriptive qualitative research approach. using literature studies and field data. The results of research on contextual mission services in the Laikit community are an approach to church service that emphasizes the importance of contextual understanding in dealing with traditional controversies. Contextual mission ministry includes all church efforts to present the message of the good news (gospel) and God's salvation in a relevant way through that tradition. Through the Missio Dei, God gives the Missio Ecclesiae, namely the authority to the church to carry out God's mission which is non-exclusive, tolerant and contextual.